Effects of oak ( Quercus ilex) tannins on digestion and nitrogen balance in sheep and goats (Small Ruminant Research, 1995)
Sheep and goats exhibited different levels of tolerance to the effects of tannins extracted from oak leaves (Quercus ilex) Feed intake, N balance, and rumen ammonia concentrations decreased by 8%, 159% and 50%, respectively, in sheep infused intraruminally with tannins (P <0.05). Similar measurements were not depressed (P> 0.05) in goats although mean rumen ammonia content was 39% less. In vivo DM digestibility was not significantly different for either sheep or goats. Averaged in vitro fermentation capacity was depressed 10% by tannin (8-12% concentration) in the rumen fluid from non-infused sheep given the same diet, but was improved by 9% for goats. Finally, tannin-infused goats lost in urine only 17% of the N ingested, while tannin-infused sheep excreted as much as 44%. The superiority of goats in dealing with tannin might result from the greater ability of their microbial population to degrade tannins, and/or their higher urea recycling and salivary secretion capabilities. Results derived from this study indicate that goats may be more suitable for grazing in oak woodland, especially during the season when alternative forage availability is scarce.